Estimating proportions of missed children and reasons for non-vaccination following implementation of “reaching the unreached” multiantigen immunization campaign—south Khyber Pakhtunkhwa, Pakistan, July–August 2023 - Ben Hamida, Amen; Alam, Fawad; Stewart, Brock; Ahmad, Shahid; Sherani, Eid Nawaz; Khan, Hafizullah; Adekunle, Akerele; Mohamed, Abdinoor; Mbaeyi, Chukwuma; Franka, Richard; Basit, Abdul; Safdar, Rana (Frontiers in Public Health, 2025)
During January 2022–June 2023, Pakistan reported 21 Wild Polio Virus 1 (WPV1) cases, all of which occurred within districts in the south Khyber Pakhtunkhwa (KP) province. In May 2023, a special immunization campaign was conducted to reach all children under 5 years of age within 69 high-risk union councils (UCs) in six districts of south KP. The campaign comprised of three rounds, each lasting 8 days, that provided bivalent oral poliovirus vaccine (bOPV) as well as other vaccines using a site-to-site delivery strategy. Rounds 1, 2, and 3 were conducted in July 2023, August 2023, and April 2024, respectively. We conducted a post-campaign evaluation (PCE) survey following the first two rounds, to assess OPV receipt, using a multistage sampling design. We analyzed PCE data for the two first rounds to provide UC-level estimates of the proportions of children who did not receive bOPV and assessed reasons for non-vaccination. The PCE survey included 8,125 children from 67 UCs during round 1 and 7,726 children from 47 UCs during round 2. The median number of villages by UC was 8 for both rounds. The median number of children by village was 16 for round 1 and 19 for round 2. Overall, 16% of children missed bOPV (95% CI = 14–18%) for round 1 [estimated total of 39,983 children (95% CI = 34,775–45,808)]; and 15% (95% CI = 13–17%) for round 2 [estimated total of 24,257 children (95% CI = 21,355–27,474)]. Percentages and numbers of missed children varied widely among UCs during both rounds. Six UCs in the first round and four UCs in the second had ≥40% missed children. Reasons for non-vaccination were similar for each round, with operational reasons leading by >60%, followed by refusals (≥20%), and child not available ( 10%). We found a high proportion of missed children during this special immunization intervention and identified the UCs with the greatest challenges. In these UCs, there is a need to design and implement comprehensive, tailored, and effective interventions for each reason why children missed vaccination.